(untitled) (e-Journal of Linguistics, 2026)
The Kakawin Ramayana is one of the most prominent literary works composed in Old Javanese poetic tradition. Within this text, Sita emerges as the central female protagonist whose position becomes marginalized when her chastity is questioned by her husband, Rama. To prove her purity, Sita is compelled to undergo masatya the act of entering a blazing fire as an ordeal of truth and fidelity. This study investigates the phenomenon of masatya in the Kakawin Ramayana using a qualitative research approach. The analysis employs Norman Fairclough’s Critical Discourse Analysis framework, encompassing three interrelated dimensions: the textual dimension (microstructural analysis), discourse practice (mesostructural analysis), and sociocultural practice (macrostructural analysis). The findings reveal that the discourse of masatya represents a form of gendered marginalization in which patriarchal authority legitimizes the control of women’s bodies and moral integrity. Simultaneously, Sita’s acceptance of the ordeal functions as a symbolic act of resistance through which she reasserts her dignity, virtue, and agency. Consequently, the Kakawin Ramayana not only reproduces patriarchal ideology but also provides a literary space in which female subjectivity negotiates power and identity.